Recurrent Urinary Tract Infection in Adult Patients, Risk Factors, and Efficacy of Low Dose Prophylactic Antibiotics Therapy - Hala Alghoraibi; Aisha Asidan; Raneem Aljawaied; Raghad Almukhayzim; Aljoharah Alsaydan; Elaf Alamer; Waleed Baharoon; Emad Masuadi; Abeer Al Shukairi; Laila Layqah; Salim Baharoon (Springer, 2023)
Abstract Background Recurrent urinary tract infection (UTI) occurs in sizable percentages of patients after a single episode and is a frequent cause of primary healthcare visits and hospital admissions, accounting for up to one quarter of emergency department visits. We aim to describe the pattern of continuous antibiotic prophylaxis prescription for recurrent urinary tract infections, in what group of adult patients they are prescribed and their efficacy. Methods A retrospective chart review of all adult patients diagnosed with single and recurrent symptomatic urinary tract infection in the period of January 2016 to December 2018. Results A total of 250 patients with a single UTI episode and 227 patients with recurrent UTI episodes were included. Risk factors for recurrent UTI included diabetes mellitus, chronic renal disease, and use of immunosuppressive drugs, renal transplant, any form of urinary tract catheterization, immobilization and neurogenic bladder. E. coli infections were the most prevalent organism in patients with UTI episodes. Prophylactic antibiotics were given to 55% of patients with UTIs, Nitrofurantoin, Bactrim or amoxicillin clavulanic acid. Post renal transplant is the most frequent reason to prophylaxis antibiotics (44%). Bactrim was more prescribed in younger patients (P < 0.001), in post-renal transplantation (P < 0.001) and after urological procedures (P < 0.001), while Nitrofurantoin was more prescribed in immobilized patients (P = 0.002) and in patients with neurogenic bladder (P < 0.001). Patients who received continuous prophylactic antibiotics experienced significantly less episodes of urinary tract infections (P < 0.001), emergency room visits and hospital admissions due to urinary tract infections (P < 0.001). Conclusion Despite being effective in reducing recurrent urinary tract infection rate, emergency room visits and hospital admissions due to UTI, continuous antibiotic prophylaxis was only used in 55% of patients with recurrent infections. Trimethoprim/sulfamethoxazole was the most frequently used prophylactic antibiotic. Urology and gynecological referral were infrequently requested as part of the evaluation process for patients with recurrent UTI. There was a lack of use of other interventions such as topical estrogen in postmenopausal women and documentation of education on non-pharmacological methods to decrease urinary tract infections.